2004
DOI: 10.1152/ajpregu.00620.2003
|View full text |Cite
|
Sign up to set email alerts
|

α-Tropomyosin mutations Asp175Asn and Glu180Gly affect cardiac function in transgenic rats in different ways

Abstract: To study the mechanisms by which missense mutations in α-tropomyosin cause familial hypertrophic cardiomyopathy, we generated transgenic rats overexpressing α-tropomyosin with one of two disease-causing mutations, Asp175Asn or Glu180Gly, and analyzed phenotypic changes at molecular, morphological, and physiological levels. The transgenic proteins were stably integrated into the sarcomere, as shown by immunohistochemistry using a human-specific anti-α-tropomyosin antibody, ARG1. In transgenic rats with either α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Extremely low levels of E180G or D175N Tm replacement had no effect on myofilament Ca 2ϩ sensitivity or relaxation function in E180G rat myocytes, while D175N Tm desensitized the myofilaments to Ca 2ϩ and accelerated relaxation rates (955). The divergent transgenic rat phenotype could be due to expressing a human ␣Tm sequence in the rat (955), but Michele et al (564) used the human ␣Tm cDNA as the backbone for mutagenesis in the previously described acute gene transfer studies which closely paralleled the work done in transgenic mouse models.…”
Section: Tropomyosinmentioning
confidence: 86%
See 1 more Smart Citation
“…Extremely low levels of E180G or D175N Tm replacement had no effect on myofilament Ca 2ϩ sensitivity or relaxation function in E180G rat myocytes, while D175N Tm desensitized the myofilaments to Ca 2ϩ and accelerated relaxation rates (955). The divergent transgenic rat phenotype could be due to expressing a human ␣Tm sequence in the rat (955), but Michele et al (564) used the human ␣Tm cDNA as the backbone for mutagenesis in the previously described acute gene transfer studies which closely paralleled the work done in transgenic mouse models.…”
Section: Tropomyosinmentioning
confidence: 86%
“…The E180G and D175N mutant Tms have been expressed in transgenic mice (567,623,706,707) and more recently in rats (955). The direct effects of the E180G Tm mutation in transgenic mice closely paralleled that of acute gene transfer, but the compensatory changes varied between E180G transgenic mouse models.…”
Section: Tropomyosinmentioning
confidence: 99%
“…A number of transgenic animal models (including mouse and rat) have been generated and extensively analyzed for all five of the original cTnT and Tm human mutations originally described by Thierfelder: I79N, R92Q, del(exon15/16), D179N and E180G [76][77][78][79][80][81][82][83]. Surprisingly, despite relatively different approaches (e.g.…”
Section: Thin Filament Mutations In Fhc: Is Flexibility the Key?mentioning
confidence: 99%
“…Studies on the Tm structure and actin binding affinity measurements have demonstrated that the HCM associated mutations often lead to alterations in the thermal stability of the Tm protein and also a decrease in actin binding affinity [25][26][27][28]. Functional characterization of muscle fibers extracted from transgenic animal models generated with the familial HCM mutations [27,29], show increased Ca 2+ sensitivity levels, which correlate well with our results in the investigation of the effects of familial HCM mutations in Tn, the results of which are reviewed elsewhere [30].…”
Section: Dcm Associated Mutations In Tropomyosinmentioning
confidence: 99%